Inspiring Anti-Tick Vaccine Research, Development and Deployment in Tropical Africa for the Control of Cattle Ticks: Review and Insights - Kasaija, Paul D.; Kirunda, Halid; Nanteza, Ann; Kabi, Fredrick; Mugerwa, Swidiq; Fuente, José de la (Vaccines, 2022)
Ticks are worldwide ectoparasites to humans and animals, and are associated with numerous health and economic effects. Threatening over 80% of the global cattle population, tick and tick-borne diseases (TTBDs) particularly constrain livestock production in the East, Central and Southern Africa. This, therefore, makes their control critical to the sustainability of the animal industry in the region. Since ticks are developing resistance against acaricides, anti-tick vaccines (ATVs) have been proposed as an environmentally friendly control alternative. Whereas they have been used in Latin America and Australia to reduce tick populations, pathogenic infections and number of acaricide treatments, commercially registered ATVs have not been adopted in tropical Africa for tick control. This is majorly due to their limited protection against economically important tick species of Africa and lack of research. Recent advances in various omics technologies and reverse vaccinology have enabled the identification of many candidate anti-tick antigens (ATAs), and are likely to usher in the next generation of vaccines, for which Africa should prepare to embrace. Herein, we highlight some scientific principles and approaches that have been used to identify ATAs, outline characteristics of a desirable ATA for vaccine design and propose the need for African governments to investment in ATV research to develop vaccines relevant to local tick species (personalized vaccines). We have also discussed the prospect of incorporating anti-tick vaccines into the integrated TTBDs control strategies in the sub-Saharan Africa, citing the case of Uganda.
Keywords: immune response; personalized vaccines; reverse vaccinology